2018
DOI: 10.1097/coc.0000000000000422
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Aerobic Fitness Assessment During Maximal and Submaximal Exercise Testing in Pediatric Oncology Patients After Chemotherapy

Abstract: This study demonstrates that the CPET can be used in pediatric cancer survivors with prior exposure to chemotherapy to demonstrate impaired cardiopulmonary exercise tolerance, which is demonstrated on submaximal and maximal effort testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In this study, we demonstrated that peak exercise performance values including pVO2, pOP, and pWR were signi cantly lower in PCS than controls, in agreement with the previous published studies [ [6][7][8][9][15][16][17][18]. Two recent studies demonstrated no signi cant difference in parameters obtained by stress echocardiogram between PCS and age-matched controls at peak exercise [19,20], suggesting that markers of ventricular myocardial performance may not always be a sensitive marker of preclinical cardiovascular abnormality and that other peripheral factors, skeletal muscle alteration and/or vascular dysfunction, may also be contributing to a reduced exercise performance.…”
Section: Decreased Exercise Performance In Asymptomatic Pcssupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we demonstrated that peak exercise performance values including pVO2, pOP, and pWR were signi cantly lower in PCS than controls, in agreement with the previous published studies [ [6][7][8][9][15][16][17][18]. Two recent studies demonstrated no signi cant difference in parameters obtained by stress echocardiogram between PCS and age-matched controls at peak exercise [19,20], suggesting that markers of ventricular myocardial performance may not always be a sensitive marker of preclinical cardiovascular abnormality and that other peripheral factors, skeletal muscle alteration and/or vascular dysfunction, may also be contributing to a reduced exercise performance.…”
Section: Decreased Exercise Performance In Asymptomatic Pcssupporting
confidence: 93%
“…Unlike echocardiogram and magnetic resonance imaging (MRI), which primarily assess cardiac function at the resting condition, CPET mainly measures the functional reserve of all organs involved in exercise performance, including heart, lung, blood, vasculature, and skeletal muscles, in which cardiac output accounts for approximately 70% of total exercise performance. Several studies have shown that PCS have a reduced exercise performance compared with age-matched normal controls [6][7][8][9], but the underlying pathophysiology of reduced exercise performance remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of using the VO 2 @RER1.0 is easy to consistently determine . Additionally, it has been shown to predict abnormal maximal VO 2 in both an anatomically normal population and pediatric cancer survivors and patients with Fabry disease . We demonstrated a novel finding that the VO 2 @RER1.0 is abnormal in the majority of individuals with SCA and that it can predict abnormal maximal VO 2 .…”
Section: Discussionmentioning
confidence: 79%
“…14 Additionally, it has been shown to predict abnormal maximal VO 2 in both an anatomically normal population and pediatric cancer survivors and patients with Fabry disease. 14,22,23 We demonstrated a novel finding that the VO 2 @RER1.0 is abnormal in the majority of individuals with SCA and that it can predict abnormal maximal VO 2 . This reflects an additional potentially useful submaximal exercise test parameter for SCA patients.…”
Section: Discussionmentioning
confidence: 82%
“…Poor cardiopulmonary tness level is known to be strongly correlated with higher risk of heart failure, cardiovascular events, and overall mortality in the general population [25,26] and in cancer survivors [27,28]. Several studies have indicated that CCS present with signi cantly reduced exercise capacity compared with the age-match control subjects, representing poor functionality, quality of life, and health status [12,14,[29][30][31][32][33]. A detailed systematic approach with peak and submaximal CPET parameters will provide a wealth of physiological information that has been underused [9,34].…”
Section: Discussionmentioning
confidence: 99%